Research Progress on the Brain Effect Mechanism of Tai Chi Chuan Training - WANG Yajun; XU Shurui; LIU Jiao (康复学报)
As a traditional exercise rehabilitation therapy in China, Tai Chi Chuan can improve the excitability of the nervous system and the ability to regulate brain functional activities. This paper summarizes the research from domestic and foreign of the brain effect mechanism of Tai Chi Chuan training, and mainly explores the effects of Tai Chi Chuan on the brainwave signal, electroencephalogram (EEG) signal (P300/N400, etc.), cerebral blood flow, cerebral blood oxygen and brain structure, brain structure and functional network using various technologies such as electroencephalo-graphy, ultrasound doppler detection, functional near infrared, and magnetic resonance imaging, which found that Tai Chi Chuan modulate different signal characteristics in multiple brain areas, providing preliminary evidence for the brain effect mechanism. Tai Chi Chuan training contributes to the improvement of attention, and the control of attention during training may be related to the regulation of α wave rhythm and activity of cerebral cortex. After Tai Chi Chuan training, the latency of P300 and N400 is shortened, and the ability of resource allocation, information processing and word processing is improved, so as to improve the capacity and resources of brain perception information. Tai Chi Chuan can improve the neuroendocrine regulation function, promote the activity of metabolic enzymes, reduce blood lipids and improve cerebral blood flow velocity. Cross-sectional studies of Tai Chi Chuan based on resting state functional MRI found that Tai Chi Chuan modulated the the brain network which is significantly associated with the training experience and the protection of cognitive function. Longitudinal studies found that Tai Chi Chuan improved the cognitive function related to the regulation of the brain structure and function of cognitive neural circuits. The study of task-state functional MRI showed that Tai Chi Chuan had a regulatory effect on the brain regions and networks which was related to memory and executive function processing. In addition, other studies showed that long-term Tai Chi Chuan training not only had plasticity changes on brain functional network, but also had plasticity changes on the volume of brain gray matter and white matter morphology. Using functional near-infrared spectroscopy, Tai Chi Chuan training was found improving executive function to be associated with the prefrontal lobe regulation. However, there are still some limitations in the present researches such as the small sample size, monomodal brain imaging, the lack of longitudinal/long-term follow-up study and lack of dose-effect relationship study, etc. Tai Chi Chuan has obtained preliminary results in the research of brain plasticity, which provides effective reference for subsequent research. In future research, multi-center, large sample and multi-modal combination will be needed to verify the current research results and further explore the brain effect related mechanisms of Tai Chi Chuan.